Pioneering Conservation Efforts with Crowdfunding Scheme for the Sumatran Tiger Conflict - Suhardono, Sapta; Mulyana, Rachmat; Prayogo, Wisnu; Suryawan, I Wayan Koko; Septiariva, Iva Yenis (Jurnal Manajemen Hutan Tropika, 2024)
Human-wildlife conflicts present significant challenges in conservation efforts. This study delves into the effectiveness of crowdfunding, intervention mechanisms, and communication initiatives in addressing the human-wildlife conflict, specifically concerning the sumatran tiger. By leveraging data from NGO web platforms, exploratory documentation, national records, and a broad spectrum of literature reviews, we aimed to unravel the nuanced dynamics of these initiatives in the conservation framework. Our findings indicate that while crowdfunding platforms such as the sapu jerat campaign offer innovative fundraising avenues, the harmonized efforts of communication strategies and robust intervention mechanisms create lasting impacts. This study underscores the essence of multifaceted approaches, stressing the value of stakeholder collaborations, including NGOs, local communities, and governmental agencies. Furthermore, this research accentuates the increasing role of digital tools in enhancing conservation efforts, suggesting a paradigm shift in contemporary conservation strategies. Hence, this study offers invaluable insights for conservationists, decision-makers, and NGOs aiming to optimize their strategies in the context of human-wildlife conflicts. At a more detailed level, the intervention mechanisms of the Sumatran Tiger Project demonstrate the importance of adaptive management, inter-agency collaboration, and sustainable financing as key components. This study highlights that the combination of technology, community involvement, strategic planning, and effective storytelling can provide a sustainable future for the sumatran tiger.